2017
DOI: 10.21037/jtd.2017.10.107
|View full text |Cite|
|
Sign up to set email alerts
|

Rhinovirus is associated with severe adult community-acquired pneumonia in China

Abstract: HRV is a common etiology in CAP among China adults, especially in severe CAP. Clinicians should be vigilant considering of the poor outcome. Highly qualified multiplex PCR techniques with invasive sampling are needed to increase the detection rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 34 publications
4
24
1
1
Order By: Relevance
“…Their findings were consistent to ours. Wang et al (15) reported that HRV was associated with severe adult CAP in Chinese; Yu et al (16) reported that human adenovirus 7 type caused higher fatality rate (28.6%) of Chinese child acute respiratory infectious disease than other types. However, their conclusions were almost drew from univariate analyses, and some confounding factors, such as underlying disease, should be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Their findings were consistent to ours. Wang et al (15) reported that HRV was associated with severe adult CAP in Chinese; Yu et al (16) reported that human adenovirus 7 type caused higher fatality rate (28.6%) of Chinese child acute respiratory infectious disease than other types. However, their conclusions were almost drew from univariate analyses, and some confounding factors, such as underlying disease, should be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…The opacities are often patchy in distribution. 80,[84][85][86][87] Bilateral involvement is fairly common, and some series in influenza pneumonia show that bilateral involvement is slightly more common than unilateral involvement. 84 On the other hand, other series in respiratory syncytial virus or coronavirus pneumonia show that unilateral involvement is more common.…”
Section: Radiological Manifestationsmentioning
confidence: 99%
“…80,85 Pleural effusions are not usual but have been reported. 87 On computed tomography of the chest, the most common pattern, ground-glass opacity, becomes even more noticeable, often in a patchy and bilateral distribution. Other patterns, such as consolidation, nodular opacities, and interlobular thickening, also can be present 86 (Figs.…”
Section: Radiological Manifestationsmentioning
confidence: 99%
“…Laboratory Studies on Initial Presentation ALT, and alkaline phosphatase to microkatals per liter, multiply by 0.0167; creatinine to micromoles per liter, multiply by 76.25; CRP to milligrams per liter, multiply by 10; total bilirubin to micromoles per liter, multiply by 17.104; and white blood cell count to ×10 9 /μL, multiply by 0.001. , Bronchoscopic, and Imaging Findings of EVALI prolonged course, with a hospital stay of 21 days, including 14 days in the ICU receiving oxygen via high flow nasal cannula. Two patients (8%) had rhinovirus on PCR testing of BAL fluid 28,29,31. Three samples (13%) had positive PCR assays for Pneumocystis jirovecii that were considered false-positives because Pneumocystis direct fluorescence antibodies were negative and the patients recovered without treatment for Pneumocystis.…”
mentioning
confidence: 99%